Hamas and ideology Sheikh Yusuf al-Qaraḍawi on the Jews, Zionism and Israel - Bartal, Shaul; Rubinsten-Shemer, Nesya (Israeli history, politics and society, 2018)
Sheikh Yusuf al- Qaraḍawi is regarded as the most influential contemporary Muslim religious figure. His best-selling book, Al-Ḥalal wal-Ḥaram fi al-Islam ("The Forbidden and the Permitted in Islam") is perhaps one of the most widely read Islamic works, after the Qur'an. The book aims to classify Qaraḍawi's thought along the axis of moderation and extremism by drawing comparisons between Qaraḍawi's teachings and those of other Muslim jurists.